Reflections on acromio-clavicular dislocations - Sarmiento, A (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2013)
A number of surgical and nonsurgical techniques have been used in the recent past for the treatment of this not uncommon traumatic condition. Thus far, no agreement has been reached regarding the method most likely to consistently render good results. Uppermost in determining the treatment has been the degree of displacement of the clavicle and the prevention of possible cosmetically unacceptable complications. Advances in the surgical care of most fractures and dislocations have lead to the current belief and practice among the majority of orthopaedic surgeons that every effort should be made to correct any deviation from the normal produced by the injury. I submit that skilful neglect and acceptance of acromio-clavicular dislocation is an option worth considering. When the dislocation is accepted, the vast majority of patients do well, functionally and aesthetically. Chronic pain is an extremely rare situation; and the resulting deformity, from the cosmetic point of view, an uncommon problem. If this is the case, what is the problem that reconstructive surgery proposes to address?
Keywords: Unnecessary Procedures; Trauma Severity Indices; Clavicle; Scapula; Humans; asymptomatické nemoci; klíční kost; akromioklavikulární kloub; ukazatel závažnosti úrazu; lidé; obnova funkce; Joint Dislocations; dislokace kloubu; osteoartróza; ortopedické výkony; procedury zbytečné; lopatka; Asymptomatic Diseases; Recovery of Function; Orthopedic Procedures; Acromioclavicular Joint; biomechanika; Biomechanical Phenomena; Osteoarthritis